Perancangan Struktur Bangunan Gedung Asrama Mahasiswi Kabupaten Landak - Prayoga, Alno; Novreza Pasha, Muhammad; Hariyani, susi; Fitriani, Nurul (Jurusan Teknik Sipil Polnep, 2023)
Observe from several urban districts in West Kalimantan they have a student dormitory as a form of local governmentsupport for the education of regional sons and daughters in Pontianak. The Landak Regency is no exception, which alsosupports the development of human resources through the construction of student dormitories in the Landak Regency.Landak Regency student dormitory will be built with 4 floors with a reinforced concrete structure. In the calculation ofthis building using the SAP 2000 application with SNI 2847-2013 for the calculation of reinforced concrete, and SNI1726-2019 for the calculation of earthquake resistance. From the calculation process, the thickness of the roof is not 12cm, floor plates 1-4 are found to be 13 cm thick. The dimensions of the beam (B1) are 25x40 cm, using field basereinforcement and 3D13 support reinforcement. For begel reinforcement, D8 reinforcement is used. The dimensions ofthe beam (B2) are 20x40 cm, using basic reinforcement for field reinforcement and support reinforcement, which is3D13. Column dimensions are 45x45 cm, using 12D16 main reinforcement. The foundation used is a pile foundationwith a depth of 20 meters with a pile dimension of 25x25 cm, and a pilecap dimension of 180 cm x 180 cm.